2021
DOI: 10.2147/ijgm.s294505
|View full text |Cite
|
Sign up to set email alerts
|

Using Integrated Bioinformatics Analysis to Identify Abnormally Methylated Differentially Expressed Genes in Hepatocellular Carcinoma

Abstract: Objective For the identification of abnormally methylated differentially expressed genes (MDEGs) in hepatocellular carcinoma (HCC), this study integrated four microarray datasets to investigate the fundamental mechanisms of tumorigenesis. Methods We obtained the expression (GSE76427, GSE57957) and methylation (GSE89852, GSE54503) profiles from Gene Expression Omnibus (GEO). The abnormally MDEGs were identified by using R software. We used the clusterProfiler package for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 54 publications
(57 reference statements)
1
4
0
Order By: Relevance
“…Therefore, the study of DNA methylation is of great signi cance for the further understanding of gene expression, ontogeny and the mechanism of the occurrence and development of diseases. Our rst study of ITGA2 methylation in tumors found that ITGA2 methylation levels were lower in cholangiocarcinoma, lung adenocarcinoma, hepatocellular carcinoma, colon cancer, and gastric cancer than in normal tissues, this is consistent with previous studies [10,[26][27]. At the same time, previous studies have shown that ITGA2 methylation levels are lower in acute myeloid leukemia, breast cancer, and thyroid cancer tumors [25,28,29].…”
Section: Discussionsupporting
confidence: 91%
“…Therefore, the study of DNA methylation is of great signi cance for the further understanding of gene expression, ontogeny and the mechanism of the occurrence and development of diseases. Our rst study of ITGA2 methylation in tumors found that ITGA2 methylation levels were lower in cholangiocarcinoma, lung adenocarcinoma, hepatocellular carcinoma, colon cancer, and gastric cancer than in normal tissues, this is consistent with previous studies [10,[26][27]. At the same time, previous studies have shown that ITGA2 methylation levels are lower in acute myeloid leukemia, breast cancer, and thyroid cancer tumors [25,28,29].…”
Section: Discussionsupporting
confidence: 91%
“…In addition, for protein expression in the human protein atlas, a web interface ( http://www.proteinatlas.org ) has been utilized to assess the role of genes in normal as well as HCC samples. Subsequently, another interface, UALCAN( http://ualcan.path.uab.edu/ ), was used for the examination of relationships between different stages of cancer for mRNA expression of the genes of interest using the TCGA set of data 43 .…”
Section: Methodsmentioning
confidence: 99%
“…uab. edu/), was used for the examination of relationships between different stages of cancer for mRNA expression of the genes of interest using the TCGA set of data 43 .…”
Section: Immune Infiltrationmentioning
confidence: 99%
“…The methylation role in gene expression was identified from 162 hypermethylated genes (downregulated) and 190 hypomethylated genes (upregulated). In biological processes, such as keratinocyte growth and calcium homeostasis, overregulated genes with poor methylation were identified [ 38 ]. PTK2, ITGA2, and VWF were found as highly expressing hypomethylated hub genes detected in the PPI network [ 38 ].…”
Section: Introductionmentioning
confidence: 99%
“…In biological processes, such as keratinocyte growth and calcium homeostasis, overregulated genes with poor methylation were identified [ 38 ]. PTK2, ITGA2, and VWF were found as highly expressing hypomethylated hub genes detected in the PPI network [ 38 ]. Three gene methylation levels, KPNA2, MCM3, and LRRC1, were linked to HCC clinical characteristics [ 39 ].…”
Section: Introductionmentioning
confidence: 99%